119 The Effect of Preload Reduction Using Head-Up Tilt Testing: An Exploratory Study Using Left Ventricular Longitudinal and Transverse Strain-Volume Loops. (3rd June 2016) - Oxborough, David; Bracknall, Tom; Lord, Rachel; Forsythe, Lynsey; Qasem, Mohammad; Mistry, Punit; Somauroo, John; George, Keith
Abstract : Introduction: Left ventricular (LV) function is dependent on intrinsic contractility and relaxation as well as the prevailing loading conditions. The Frank-Starling mechanism states that absolute myocardial shortening would be lower in the presence of a reduced preload, however LV function is complex and must adapt in this setting in order to maintain stroke volume and cardiac output. The impact of preload reduction on cardiac mechanics has been scarcely explored however the direct relationship of strain (s) in different planes and simultaneous volume assessment has not been assessed. This exploratory study utilises a novel technique (s-volume loops) in order to establish the relative temporal contribution of longitudinal (Ls) and transverse strain (Ts) to volume change throughout the cardiac cycle following 1 and 5 min of head-up tilt testing. Methods: Five healthy subjects underwent standard transthoracic echocardiography to obtain an apical 4 chamber orientation with a focus on the LV in a supine position and following 1 min and 5 min of head-up tilt testing. As well as a standard assessment, raw temporal Ls and Ts values were exported and divided into 5% time increments across the cardiac cycle. Concomitant LV volumes were traced at each 5% time increment to provide simultaneous s-volume loops. The s-volume relationship was assessed by 1) polynomial equations to derive absolute strain values for% end diastolic volumes (EDV) and 2) systolicï¿½diastolic coupling (SDcoup) as the difference between systolic and diastolic strain within the same working range of% EDV. Results: There was a significant reduction in EDV at 1 min of head-up tilting (92ï¿½16ml Vs. 64ï¿½6ml) with no further change at 5 min. There was no significant change in EF or effective stroke volume. There was a reduction in peak Ls at 1 min tilting (-16ï¿½1 Vs. -12ï¿½1%) which remained stable at 5 min. Conversely, there was a gradual increase in Ts across time (16ï¿½3 Vs. 37ï¿½11%) as well as a gradual reduction in the time to peak Ts. Following calculation of s-volume loops the paradoxical relationship of reduced Ls and a concomitant increase in Ts remained at all 10% increments of EDV. There was a marked increase in Ts SDcoup at all 10% EDV increments at 5 min post tilt. Conclusion: Preload reduction as a consequence of head-up tilt testing results in a shift in cardiac mechanics with a reduction in longitudinal and concomitant increase in transverse contribution to volume reduction and maintenance of EF. The systolic-diastolic coupling suggests that LV filling in the setting of a reduced preload is maintained by a greater return to original length of the myocardium in the transverse plane for any given volume. These findings provide important physiological value when assessing LV function in the clinical setting where a reduction in preload is evident.